Effects of a marine heatwave on adult body length of three numerically dominant krill species in the California Current Ecosystem. (10th November 2021) - Killeen, Helen; Dorman, Jeffrey; Sydeman, William; Dibble, Connor; Morgan, Steven
Abstract: Krill are an abundant and globally distributed forage taxon in marine ecosystems, including the California Current Ecosystem (CCE). The role of krill in trophodynamics depends on both abundance and size (biomass), but the impact of extreme climate events on krill body size is poorly understood. Using samples collected from 2011 to 2018, we tested the hypotheses that adult body length of three krill species ( Euphausia pacifica, Thysanoessa spinifera, and Nematoscelis difficilis ) declined during the 2014–2016 Northeast Pacific marine heatwave/El Niño event due to elevated seawater temperatures, reduced upwelling, and low primary productivity. Hierarchical mixed-effects modelling showed that mean length of adult E. pacifica and T. spinifera declined and N. difficilis length increased during 2015. These trends differed by sex and reverted to a pre-heatwave state in 2016. Temperature, upwelling, and food availability (chlorophyll- a content) did not explain decreased length in 2015, but environmental drivers of length varied regionally and by sex across all years. This study documents the impact of a major marine heatwave (MHW) on adult krill length in one of the world's major upwelling systems and indicates how pelagic ecosystems may respond to increasingly frequent MHWs.